A (in)eficácia do sistema normativo florestal no Brasil: um olhar para as raízes do problema e um encontro com a refundação da jurisdição - Pinto, Ana Cláudia Favarin (2022)
The present work aims to investigate the evolution of forest legislation, as well as to point out the problematic points of the norm, to perceive the (in)effectiveness of the forest norm and to propose the perspective of the refoundation of the jurisdiction. To make this possible, the work is divided into three main sections. It begins with the mapping of the Brazilian forest regulatory system from the mid-20th century onwards, in an attempt to highlight the negative aspects of the 2012 Forest Code, analyzing the Direct Actions of Constitutionalities proposed in the face of it. The second chapter verifies the confrontation of environmental issues by the impact of environmental legislation regarding forests in the judicialization, as well as the exemplification of the problem through two jurisprudence selected within the scope of TRF1. Finally, the third section studies the proposal for the refoundation of jurisdiction as an alternative to the (in)effectiveness of environmental regulations in relation to forests. In the environmental field, the phenomenon of judicialization demonstrates its relevance, especially due to the position of the Judiciary in preserving the environment. Thus, the present work intends to answer the following question: facing the Brazilian judicialization of environmental issues related to forests and, taking as a reference the study of the (in)effectiveness of the forestry norm, how the proposals made by the Refoundation of Jurisdiction can contribute to a change in the normative protection of forests paradigm? Based on the research problem transcribed, the research intends to investigate the evolution of forest legislation, as well as point out the problematic points of the norm, to perceive the (in)effectiveness of the forest norm and to propose the perspective of the refoundation of the jurisdiction. To solve the research problem raised, the phenomenological-hermeneutic approach is used, as a science that establishes interpretation assumptions that will lead the hermeneutist to the understanding of a certain fact, behavior or norm. As a base theory, the work has the hermeneutic theory, working the thesis of the refoundation of the jurisdiction of Angela Araújo da Silveira Espindola, using the contributions of authors such as Lênio Luiz Streck and Dierle Nunes. At the end of the research, it is possible to conclude that the current forest regulation is ineffective, with the possibility of refounding the jurisdiction as a way to restructure the bases of forest legislation, focusing on the construction of forest sustainability. Thus, it is necessary to rethink and refound jurisdiction, moving away from decisions that harm environmental protection, based on economistic standards, which meet the objectives of environmental protection and sustainability.